2023
DOI: 10.1039/d2va00319h
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Fe–N–C nanoparticles as a dual nanozyme for label-free colorimetric detection of antibiotics

Abstract: In this study, we reported a simple one-step pyrolytic strategy for fabrication of N-C codoped Fe-based nanoparticles (Fe-N-C) and exhibited their oxidase-mimic and peroxidase-mimic activity in a chromogenic reaction with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…With this principle, several studies have been reported to develop nanozyme catalysis-based assays of antibiotics. 137–140,150 Che et al synthesized three shapes of g-C 3 N 4 with different peroxidase and fluorescence properties via adjusting the degrees of planar connectivity and interlayer stacking. 150 To improve enzymatic activity and amplify the difference in signals toward different antibiotics, in situ growth of an equivalent amount of MIL-101(Fe) on the three morphologies of g-C 3 N 4 was performed.…”
Section: Detection Of Environmental Pollutants Based On Nanozyme Cata...mentioning
confidence: 99%
“…With this principle, several studies have been reported to develop nanozyme catalysis-based assays of antibiotics. 137–140,150 Che et al synthesized three shapes of g-C 3 N 4 with different peroxidase and fluorescence properties via adjusting the degrees of planar connectivity and interlayer stacking. 150 To improve enzymatic activity and amplify the difference in signals toward different antibiotics, in situ growth of an equivalent amount of MIL-101(Fe) on the three morphologies of g-C 3 N 4 was performed.…”
Section: Detection Of Environmental Pollutants Based On Nanozyme Cata...mentioning
confidence: 99%